O processo de subjetivação profissional durante os estágios supervisionados em psicologia - Pires, Viviane Silva (2011)
Internship is legally understood in Brazil as an overseen educational activity to be developed in a work setting aiming to prepare students to make productive work. According to the federal law number 11.788/08, its main aim is to provide students with competences directly related to the professional activity in a curricular context and to make students develop themselves to live as citizens and to work professionally. With a focus on the professionalizing internship, this research aimed at understanding the professional subjectiveness process of Psychology undergraduates at a public university in the state Minas Gerais during their internship and according to a critic perspective in schooling psychology. The importance of studying psychologist academic training above all the relationship between theory and practice is on the fact that the internship is his/her initial contact with the professional experience itself after four years of theoretical studies. Understood as a way of appropriating and internalizing theoretical and practical dimensions related to the psychologist profession and constructed by the individual, the concept of professional subjectiveness is viewed in the light of the cultural-historical theory, that is, as a result of the human being social constitution. Three Psychology s intern students and their respective overseers were interviewed during their internship period to talk about the process of professional constitution at this phase of the academic training. To do so, oral history proved to be an important methodological support, for it offers a means of giving voice to common people and letting them signify their multi-circumstantial experiences. Results reiterate the presence of subjectivity in the dynamics of an undergraduate training, but they showed that it is permeated by social relations established in his/her personal life story and professional trajectory, stemming from the professional choice, the relationship between intern and overseer, the professional activity properly considered, the psychotherapy, the rules, and from the institutionalization of knowledge, among others aspects that guide the professional subjectiveness during the internship. We verified that the training of a Psychology undergraduate includes multiple determinations that exceed the academic setting because it points out the breaking down of the professional dimensions and personal one dichotomy.